Analisis Kesiapan Guru Dalam Menghadapi Pembelajaran Berbasis Teknologi di SDN 002 Samarinda Utara - Khairunisa, Ratna; Hikmah, Nurul; Febriani, Ami (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Information and communication technology is a part of science and technology which is generally related to the retrieval, collection, processing, storage, dissemination and presentation of information. The existence of information and communication technology can make it easier for anyone to learn and get the information they need from various sources, at any time and wherever they are. This research aims to determine teacher readiness in facing technology-based learning at SDN 002 North Samarinda. This research uses a qualitative research method with a descriptive approach and uses interview, observation and documentation techniques. The results of this research found that teacher readiness at SDN 002 North Samarinda was quite good, but the lack of infrastructure made technology-based learning at State Elementary School 002 North Samarinda less than optimal. Thus, it can be concluded that teacher readiness is quite good, the availability of technology-based learning infrastructure is good, but implementation is less than optimal due to the lack of technology-based learning infrastructure, namely LCD projectors.